P652 Compare risk factors associated with infectious complication in Crohn's disease with and without preoperative infliximab. (25th January 2019) - Ge, X; Cao, Q; Zhou, W
Abstract: Background: Infliximab therapy plays important roles in Crohn's disease (CD). The relationship between infliximab and infectious complications are still unclear. Our aim was to clarify this relationship and to compare the risk factors to predict infectious complications in CD with and without preoperative infliximab. Methods: 390 CD patients undergoing surgery from June 2014 to June 2018 were eligible. Postoperative complications were compared in patients with and without preoperative infliximab. Univariate and multi-variate analyses were performed to identify risk factors for infectious complications. Receiver-operating characteristic curves were performed to examine the cut-off value of predictors in infectious complications. Results: 85 CD patients received infliximab within 8 weeks of surgery. 129 patients had postoperative complications, with 35 receiving infliximab. No significant difference of postoperative complications was found in CD patients with and without infliximab ( p = 0.073). However, CD patients receiving preoperative infliximab suffered more infectious complications ( p = 0.010). Preoperative infliximab was confirmed to be an independent risk factor in infectious complications ( p = 0.042). Multi-variate analysis suggested that erythrocyte sedimentation rate was an independent risk factor associated with infectious complications in patients receiving preoperative infliximab ( p = 0.022), and C-reactive protein was an independent risk factor in patients not receiving preoperative infliximab ( p = 0.019). Conclusions: Preoperative use of infliximab ≤ 8 weeks was independently associated with infectious complications in CD. Preoperative erythrocyte sedimentation rate and C-reactive protein could predict infectious complications in CD with and without infliximab. Different risk factors associated with postoperative infectious complications in CD exposed and unexposed to infliximab should be noticed.